The mechanical properties of 3D-printed metakaolin/fly ash-based geopolymer mortars containing multi-walled carbon nanotubes exposed to freeze-thaw - Tanyildizi, Harun; Oncu, Mehmet Emin; Seloglu, Maksut; Coskun, Ahmet (Wiley, 2026)
This study examined the mechanical properties of 3D-printed geopolymer mortars (GPMs) containing multi-walled carbon nanotubes (MWCNTs) subjected to freeze-thaw (F-T). The fly ash (FA) and metakaolin (MK) were used as binders in the 3D-printed geopolymer composites (GPCs). MWCNT was used at 0%, 0.25%, 0.5%, and 0.75% rates in the mixtures. The rheological characteristics of the mixtures were ascertained through experiments conducted on viscosity, buildability, and flow. After this stage, samples with dimensions of 40 x 40 x 160 mm were manufactured using a 3D printer and cured for 28 days at a laboratory temperature of 20 +/- 2 degrees C. Then, 3D-printed geopolymer (3DPG) samples were subjected to the F-T in accordance with the TS EN 15177 standard. Finally, the weight loss (WL), compressive strength (CS), flexural strength (FS), and ultrasonic pulse velocity (UPV) of 3DPG specimens exposed to F-T were determined. Additionally, scanning electron microscopy (SEM), x-ray powder diffraction (XRD), and energy dispersive x-ray spectroscopy (EDX) analyses were carried out on specimens. The results of this investigation showed that 3D-printed GPM containing 0.25% MWCNT had the highest FS, UPV, and CS. Furthermore, this study demonstrated that the 3D-printed GPM with 0.25% MWCNT has a strong resistance to F-T with a CS retention rate of 95.86%.
Keywords: 3D-printing; freeze-thaw; geopolymer mortar; mechanical properties; multi-walled carbon nanotube; rheology